Alloying with Mn enhances the activity and durability of the CoPt catalyst toward the methanol oxidation reaction - Deshpande, Pooja; Prasad, Bhagavatula L. V. (ACS Applied Materials & Interfaces, 2023)
To improve the catalytic performance and durability ofPt catalystsused for the methanol oxidation reaction (MOR) in direct methanolfuel cells (DMFCs), alloying of Pt with other transition metals suchas Ru, Co, Ni, and Fe is considered an effective approach. Despitethe significant progress made in the preparation of bimetallic alloysand their utilization for MOR, improving the activity and durabilityof the catalysts to make them commercially viable remains a stiffchallenge. In this work, trimetallic Pt100-x (MnCo)( x ) (16 < x < 41) catalysts were successfully synthesized via borohydridereduction followed by hydrothermal treatment at 150 & DEG;C. The electrocatalyticperformance of the synthesized trimetallic Pt100-x (MnCo)( x ) (16 < x < 41) catalysts toward MOR was studied using cyclicvoltammetry and chronoamperometry. The results affirm that all Pt100-x (MnCo)( x ) (16 < x < 41) alloys have superior MOR activityand durability as compared to bimetallic PtCo alloys and commerciallyavailable Pt/C (comm. Pt/C) catalysts. Among all the compositionsstudied, the Pt60Mn1.7Co38.3/C catalystexhibited superior mass activity (1.3 and 1.9 times higher than thoseof Pt81Co19/C and comm. Pt/C, respectively)toward MOR. Furthermore, all the newly synthesized Pt100-x (MnCo)( x )/C (16 < x < 41) catalysts showed better CO tolerance when comparedwith comm. Pt/C. This improved performance of the Pt100-x (MnCo)( x )/C (16 < x < 41) catalyst can be attributed to the synergisticeffect of Co and Mn on the Pt lattice.
Keywords: CO tolerance; direct methanol fuel cells; electrocatalysis; methanol oxidation reaction(MOR); trimetallic alloy catalysts